Islam, Depoliticization and the European Crisis of Democratic Legitimacy - Doyle, Natalie J. (Politics, religion & ideology, 2013)
A new form of political discourse hostile to Islam has been gaining ground in Europe. Initiated by neo-nationalist parties it appeals to liberal values and is now penetrating mainstream politics. The recent French presidential campaign threw light on the way Centre Right parties vying for government are increasingly instrumentalizing hostility towards Islam to respond to the political crisis triggered by the problem of public debt across the European Union. Critics are approaching this phenomenon through the lens of Foucault's notion of governmentality, questioning the assertion that Muslims cannot integrate in European societies because of their religion and highlighting the failure of European nation states to treat them as citizens and promote their socio-economic inclusion. This perspective yields valuable insights: it shows how the presence of Muslims challenges the belief of European societies in their self-perceived rationality and tolerance, resting on their commitment to secularity as epistemic category. The strident defense of secularism that accompanies Islamophobia is part of the discourse of securitization that characterizes the neo-liberal form of contemporary governmentality and promotes the de-politicization of social problems. The notion of governmentality, however, cannot account fully for the root-cause of Islamophobia: the loss of collective purpose that has triggered a crisis of government and seen the concern for efficient governance to erase the goal of collective self-determination. At heart, Islamophobia constitutes a manifestation of the European states' crisis of democratic legitimacy.